KOMUNIKASI INTERPERSONAL JARAK JAUH MAHASISWA RANTAU ASAL KALIMANTAN FISIP UNISRI DENGAN ORANG TUA DALAM MENJAGA HUBUNGAN HARMONIS MELALUI WHATSAPP - Umbaran, Febri; Sihabuddin, Sihabuddin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
The development of communication technology has transformed the way individuals interact, including the relationships between Kalimantan-origin students studying at Slamet Riyadi University Surakarta and their parents. WhatsApp has become the primary medium for maintaining long-distance interpersonal communication between students and parents to preserve a harmonious relationship. This study aims to understand how long-distance interpersonal communication between children and parents helps maintain a harmonious relationship through WhatsApp. The research applies Joseph A. DeVito’s interpersonal communication theory, which emphasizes the importance of openness, empathy, support, a positive attitude, and equality in interpersonal interactions. The research method used is descriptive qualitative with a phenomenological approach. Data were collected through in-depth interviews with Kalimantan-origin students studying at the Faculty of Social and Political Sciences at Slamet Riyadi University Surakarta and their parents. The findings indicate that WhatsApp plays a crucial role in maintaining communication between students and parents. High-intensity communication through text messages, voice calls, and video calls enables students to stay emotionally connected with their parents. Elements of openness, empathy, support, a positive attitude, and equality serve as key aspects in sustaining a harmonious relationship. Despite challenges such as differences in communication patterns and technical disruptions, regular communication through WhatsApp helps students feel closer to their parents. Furthermore, students who engage in open communication with their parents tend to feel more supported and motivated in their lives away from home.komponen yang sama dengan di abstrak dalam versi bahasa Indonesia.